“Sociocultural changes and continuities of the Ashéninka of Ponchoni (great pajonal)” - Vílchez Jiménez, Elsa (2013)
We present the different ways in wich various Ponchoni’s social actors are inserted in the larger society and how the changes have been given around them in order to look in to the asheninka identity characteristics. We include an andean person.